Toward sustainable electricity consumption in Brazil: the role of economic growth, globalization and ecological footprint using a nonlinear ARDL approach - Rafindadi, Abdulkadir Abdulrashid; Usman, Ojonugwa (Routledge Journals, Taylor & Francis Ltd, 2021)
This study investigates nonlinear effects of economic growth, globalization and ecological footprint on sustainable electricity consumption in Brazil using monthly time-series data from 1971M:01 to 2014M:12 and a nonlinear ARDL model. The results show that the effects of economic growth, globalization and ecological footprint on electricity consumption are asymmetric. A positive shock to economic growth increases electricity consumption more than a negative shock of the same magnitude causes electricity consumption to decline. In the case of globalization, the effect of a negative shock is stronger. Furthermore, the long-term effects of positive and negative shocks to the ecological footprint are negative but statistically significant only in the case of a positive shock while in the short term, the increasing effect of a positive shock to the ecological footprint is stronger than the reducing effect of a negative shock of the same magnitude. These findings are validated when globalization is disaggregated to economic, political and social dimensions.
Keywords: electricity consumption; ecological footprints; globalization; nonlinear asymmetric causality test